Male wage inequality and marital dissolution: Is there a link? - Andriana Bellou (Institute for the Study of Labor (IZA), 2013)
After almost a century-long pattern of rising marital instability, divorce rates leveled off in 1980 and have been declining ever since. The timing of deceleration and decline in the rates of marital disruption interestingly coincides with a period of substantial growth in wage inequality. This paper establishes a connection between the two phenomena and explores potential explanations for the underlying link. Using individual data on female marital histories in a duration analysis framework combined with regional and temporal variation in the pattern of male wage dispersion, I show that inequality has a significant stabilizing effect on the marital relationship. Quantitatively, increases in male wage dispersion can roughly explain up to 30% of the fall in the mean separation probability between 1979 and 1990. Several plausible explanations for this relationship are assessed: changes in spousal labor supplies, female wage inequality, income uncertainty, social capital as well as a hypothesis of on-the-marriage search. The results are most supportive of the search interpretation. No strong quantitative support was found for the remaining mechanisms.
Keywords: J11; J12; J31; 330; divorce; wage inequality